2019
DOI: 10.1155/2019/2815301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound-Guided Subcostal Transversus Abdominis Plane Block and Quadratus Lumborum Block in Laparoscopic Cholecystectomy: A Prospective, Randomized, Controlled Clinical Study

Abstract: Background. The aim of this study was to compare the effectiveness of ultrasound-guided (USG) subcostal transversus abdominis plane (TAP) block and quadratus lumborum (QL) block as preventive analgesia methods after laparoscopic cholecystectomy. Methods. A total of 120 patients, 18–75 years of age, were separated into 2 groups preoperatively. Patients in group TAP (n = 60) received 0.3 ml/kg bupivacaine with USG bilateral subcostal TAP block; patients in group QL (n = 60) received 0.3 ml/kg bupivacaine with US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 13 publications
(14 reference statements)
1
46
0
Order By: Relevance
“…A total of 135 relevant studies were initially detected, and 8 studies [11][12][13][14][15][16][17][18] were eventually included,comprising 564 patients. The process and results of the literature screening are shown in Fig.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 135 relevant studies were initially detected, and 8 studies [11][12][13][14][15][16][17][18] were eventually included,comprising 564 patients. The process and results of the literature screening are shown in Fig.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…One study [17] did not mention the blind method employed for the subjects.The researchers used the blind method as well as the rest. Three studies[14, 16,18]made use of blinding for outcome measurements, and five other studiesdid not. In addition, all studies reported the completion of the trial and no withdrawals.Only one study [18] reported other high biases.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound-guided QLB technique was first described by Blanco [11,12], and the benefits of QLB for postoperative pain relief and opioids-sparing effect have been reported by several randomized controlled trials and case reports [2,5,6,[8][9][10][19][20][21][22][23][24][25][26][27][28][29][30]. All approaches have been proved the synergistic efficacy for multimode analgesia, especially for QLB2 or QLB3 after laparoscopic surgery, cesarean section and total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%